Media Documentary Films First Aid for Willpower Enhancement First Aid Burn Case - Rida Darotin; Eky Madyaning Nastiti; Feri Ekaprasetia; Yunita Wahyu Wulansari; Guruh Wirasakti (Universitas STRADA Indonesia, 2026)
Background: Burns are one of the injuries that can affect children. Children aged 5-14 years are the age in growth and development to develop gross motor skills that have a high risk of injury. School-age children aged 6 years have higher assumptions about their physical abilities while for ages 7-12 years have limitations in understanding related to personal safety, even though adolescent children should be able to perform first aid. Purpose: to identify students' willpower to giving first aid for burns before the documentary film is screened, to identify students' willpower to giving first aid for burns after the documentary film is screened and analyze the difference on students' willpower to giving first aid for burns before and after screened of the Documentary Film giving first aid for burns. Methods: The study used the quasi experimental method with one group pretest-post test design. The sample of this study was 96 grade eight students of SMPN 1 Kalisat using a simple random sampling technique. Instrument of the research used questionnaire and media audiovisual. The questionnaire used to measure willpower variables. Media audiovisual used documentary film. The duration of the documentary film is 10 minutes and this is shown 3 times for 1 hour. Results: Data analysis using the Mc Nemar test with a P Value of 0.00 means that there is a difference on students' willpower to giving first aid for burns before and after screened documentary films. Conclusion: Before the documentary film was screened, most students hadn't had the willpower to giving first aid for burns, After the documentary film was screened, most students had the willpower to giving first aid for burns, and there was a difference on students' willpower to giving first aid for burns before and after screened documentary films.